Iowa Birdline update, February 13, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for February 13, 1989. Highlights include sightings of a Slaty-backed Gull, an Evening Grosbeak and an albino Barred Owl. Epson - sheet feed/flatbed